Kajian Penempatan Kapasitor Bank Menggunakan Metode Genetik Algoritma Pada South Balam Feeder 1 PT. Chevron Pacific Indonesia - Akto Sello; Edy Ervianto; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Reactor power losses in electric power networks can be compensated by capacitor bank. With a capacitor bank the voltage in the line keep in standard tolerance. In PT Chevon Pacific Indonesia, South Balam Feeder 1 with 13,8 kv radial distribution network and total load 4470 kVA is inductive motor of nod pump distributed at a number of dot with length 44.7 km. When The length of electric power networks longer, the problem is about size of capacitor and it’s located to get the minimum power losses. This case study will give one of solution with Algorithm Genetic Methode using software ETAP 7.0 and Matlab 2008b. The mounting points on 16 Z 14, SoBalam#155, 16 Z 73, SoBalam#142 and Antara#7 with capacity 600 kVAr and then system of voltage 95 % over the nominal voltage as the result.Keywords : power flow, genetic algorithms, reactive power compensation, power quality, capacitor bank.